Characterization of antimicrobial, antioxidant, anticancer properties and Chemical composition of Malaysian andrographis paniculata leaf extract - Lee Seong Wei; Wendy Wee (2011)
This study was carried out to characterize antimicrobial and antioxidant activities of Malaysian Andrographis paniculata leaf extract. The main objective of the present study is to reveal the potential of A. paniculata leaf to be used as antimicrobial and antioxidant agent for aquaculture feed use. Antimicrobial property of A. paniculata leaf extract against Aeromonas hydrophila, Escherichia coli, Edwardsiella tarda, Flavobacterium sp., Klebsiella sp., Salmonella sp., Vibrio alginolyticus, V. parahaemolyticus, V. cholerae and Pseudomonas aeruginosa. was revealed by using broth micro-dilution method whereas anticancer activity of the extract was determined with Colorimetric MTT (tetrazolium) assay against human breast adenocarcinoma (MCF-7). Compounds of the plant extract were screening and identified by using gas chromatography-mass spectrometry (GC-MS). Antioxidant activity of the plant extract was also characterized by using α, α-diphenyl-β-picrylhydrazyl (DPPH) radical scavenging method. The result of the present study showed that A. paniculata leaf extract possesses antimicrobial, antioxidant and anticancer activities. The minimum inhibitory concentration (MIC) values were ranged from 31.25 to 125 mg/l in which the plant extract was found can inhibit the growth of Edwardsiella tarda Escherichia coli, Flavobacterium sp., Pseudomonas aeruginosa and Vibrio cholerae at 31.25 mg/l, Aeromonas hydrophila, Klebsiella sp, Salmonella sp. and Vibrio alginolyticus at 62.5 mg/l and it was able to control the growth of and Vibrio parahaemolyticus at 125 mg/l. The plant extract’s antioxidant activity was recorded almost same like Quercetin at the concentration of 10 ppt whereas the value of IC50 of the plant extract against MCF-7 cell was 20.72 ± 1.10 μg/ml. A total of 16 chemical compound were identified (n-hexadecanoic acid, 7.65 %, 9,12,15- Octadecatrienoic acid, methyl ester, (Z,Z,Z)-, 6.58 %, β-sitosterol, 6.35 %, α-DGlucopyranoside, methyl, 5.12 %, 9,12,15-Octadecatrienoic acid, ethyl ester, (Z,Z,Z)- 5.05 %, 2H-1-Benzopyran-6-ol,3,4-dihydro-2,8-dimehtyl-2-(4,8,12-trimethyltridecyl)- 4.20 %, Phytol, 4.17 %, Pentadecanoic acid, 14-methyl-, methyl ester, 3.47 %, Methyl 2-O-benzyl-β- D-xylopyranoside, 2.68 %, 9, 12-Octadecadienoic acid (Z, Z)-, 2.61 %, 3-phenylpropanoic acid, 4-hexadecyl ester, 2.48 %, Heneicosanoic acid, 9,12-Octadecadienoic acid, methyl ester, (E,E)-, 1.72 %, Oleic acid, 1.72 %, Cholest-5-en-7-one, 3-fluoro-, (3 β)-, 1.61 %, Glycerin, 1.27 % and 4H-Chromene-3-carbonitrile, 2-amino-7-benzyloxy-4-cyclohex-3- enyl-, 1.10 %). The findings of this study indicating that methanol extract of A. paniculata leaf extract possess high antimicrobial and antioxidant properties.